PENERAPAN METODE TOTAL PHYSICAL RESPONSE (TPR) UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KOSAKATA BAHASA MANDARIN SISWA KELAS VIII SMP LKIA PONTIANAK - Nafiki, Dinda Camelia Meidita; Thamrin, Lily; Lusi, Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
Vocabulary is a very important role in Chinese. Mastering vocabularycan improve students' listening, speaking, reading and writing skills.In order to create a good learning process, teachers can use interestingteaching methods to support students' learning interests, especiallysuitable vocabulary teaching methods should be selected, for example:total physical response method. total body response method is aforeign language teaching method, which teaches language throughthe coordination of language and movement. In order to understandwhether the use of total physical response method can effectivelyimprove students' understanding of Chinese words, the authorconducted a study on the second grade students of LKIA MiddleSchool. Based on the results showed that the students' ability tounderstand Chinese words improved after using total physicalresponse method. The average score of the students in the pre-test was66%, and the average score in the post-test was 86%, indicating thatthe students understanding of Chinese words had improved by 23%.Therefore, using the total physical response method can improve thestudents' understanding of Chinese words on the second grade studentsof LKIA Middle School.